Insomnia symptoms and incident heart failure: a population-based cohort study. (15th August 2021) - Mahmood, Asos; Ray, Meredith; Dobalian, Aram; Ward, Kenneth D; Ahn, SangNam
Abstract: Aims: Heart failure (HF) is an ongoing epidemic and a serious clinical and public health issue. Currently, little is known about prospective associations between insomnia symptoms and HF incidence. We investigated the longitudinal associations between time-varying insomnia symptoms (difficulty initiating sleep, difficulty maintaining sleep, early-morning awakening, non-restorative sleep) and incident HF. Methods and results: Data were obtained from the Health and Retirement Study in the US for a population-representative sample of 12, 761 middle-aged and older adults (age ≥ 50 years; mean [SD] age, 66.7 [9.4] years; 57.7% females) who were free from HF at baseline in 2002. Respondents were followed for 16 years for incident HF. We employed marginal structural discrete-time survival analyses to adjust for potential time-varying biological, psycho-cognitive, and behavioral factors and to account for bias due to differential loss to follow-up. At baseline, 38.4% of the respondents reported experiencing at least one insomnia symptom. During the 16-year follow-up, 1, 730 respondents developed incident HF. Respondents experiencing one (hazard ratio [HR]=1.22; 95% CI: 1.08–1.38), two (HR=1.45; 95% CI: 1.21–1.72), three (HR=1.66; 95% CI: 1.37–2.02), or four (HR=1.80; 95% CI: 1.25–2.59) insomnia symptoms had a higher hazard of incident HF than asymptomatic respondents. Respondents that had trouble initiating sleep (HR=1.17; 95%CI: 1.01–1.36), maintaining sleep (HR=1.14; 95% CI: 1.01–1.28), early-morning awakening (HR=1.20; 95% CI: 1.02–1.43), or non-restorative sleep (HR=1.25; 95% CI: 1.06–1.46) had a higher hazard of incident HF than asymptomatic respondents. Conclusion: Insomnia symptoms, both cumulatively and individually, are associated with incident HF. Public health awareness and screening for insomnia symptoms in at-risk populations should be encouraged to reduce HF incidence. Graphical Abstract: